Determination of sulfonylureas in cereal samples with electrophoretic method using ionic liquid with dispersed carbon nanotubes as electrophoretic buffer - Springer, Valeria Haydee (2013)
A capillary electrophoresis method to determine four sulfonylureas in grain samples was developed using 10 mM of 1-butyl-3-methyl imidazolium tetrafluoroborate (bmin BF4) as electrophoretic buffer solution. 2 mg L 1 of Surfactant Coated-Single Wall-Carbon Nanotubes (SC-SWCNTs) was added to the buffer solution to improve the resolution. In this way, the separation of nicosulfuron, ethoxysulfuron, sulfometuron methyl and chlorsulfuron was carried out in 16 min without using organic solvents. A clean up-precon-centration procedure was done prior to inject the sample into the CE instrument, in order to achieve the established maximum residue limits (MRLs). So, the detection limits (LODs) for each analytes were between 16.8 and 26.6 lg kg 1. The relative standard deviations (RSDs) were in the range 1.9-6.7%. A recovery study using the so-called matrix matched calibration demonstrates that no matrix interferences were found throughout the determination. The recovery percentages were ranged between 80% and 113%.